1992
DOI: 10.1080/10473289.1992.10466968
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Concentrations of Trivalent and Hexavalent Chromium from Contaminated Soils at Unpaved and Partially Paved Commercial/Industrial Sites

Abstract: The primary health hazard to people in areas surrounding contaminated sites is often believed to be exposure to airborne contaminants. Due to insensitive sampling or analytical methods for many chemicals, including hexavalent chromium [Cr(VI)], the only option available for quantifying the hazard posed by ambient airborne concentrations of these chemicals has been limited to predictions based on various modeling approaches. Due to the use of compounded worst-case input parameters in the models, the resulting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Based on the work by Sheehan et al, 4 the anticipated airborne concentrations of Cr(vi) in the Windsor airshed were then expected to be 1-5 ηg/m 3 for both the outdoor and indoor environments. These figures would also be in agreement with the published work of Falerios et al 8 who found that background levels of Cr(vi) of perhaps 1-4 ηg/m 3 exist in urban air as a result of a variety of anthropogenic sources. The MOEE first implemented the new Cr(vi) methodologies during this study.…”
Section: The Windsor Air Quality Studysupporting
confidence: 82%
“…Based on the work by Sheehan et al, 4 the anticipated airborne concentrations of Cr(vi) in the Windsor airshed were then expected to be 1-5 ηg/m 3 for both the outdoor and indoor environments. These figures would also be in agreement with the published work of Falerios et al 8 who found that background levels of Cr(vi) of perhaps 1-4 ηg/m 3 exist in urban air as a result of a variety of anthropogenic sources. The MOEE first implemented the new Cr(vi) methodologies during this study.…”
Section: The Windsor Air Quality Studysupporting
confidence: 82%
“…The aboriginal people of the Cold Lake First Nations belong to the Dene Suline tribe, whose traditional lands ranged from south of Bonnyville, Alberta to the northernmost point at Peter Pond Lake, Saskatchewan. The area has a humid continental climate, with a lower than average rainfall compared to other Canadian cities, and contains many unpaved roads that can contribute to airborne dust particles (Falerios et al, 1992;Gómez et al, 2005;James et al, 2012). Local bedrock geology is predominantly marine shale of the Lea Park Formation from the Upper Cretaceous (Prior et al, 2013) overlain by various fluvial sediments and glacio-fluvial tills (Fenton and Andriashek, 1983).…”
Section: Study Areamentioning
confidence: 97%
“…This industrial site sampling program has been described in detail elsewhere. 2,4 These samples were collected and analyzed using the ASTM Standard Test Method D 5281-92 for the collection of airborne Cr(VI) and the EPA SW-846 Method 6010 for the collection of total chromium and TSP. 27 The main purpose of this sampling effort was to characterize the ambient air concentrations of Cr(VI) and total chromium at each site.…”
Section: Selection Of Sites Evaluatedmentioning
confidence: 99%
“…In order to quantitatively address the potential inhalation hazards posed by this material, hundreds of air samples were collected and analyzed for Cr(VI) at these sites using a sensitive new method, American Society of Testing and Materials (ASTM) Standard Test Method D 5281-92, developed specifically for this purpose. [2][3][4] Additionally, concentrations of Cr(VI) in surface soil were characterized at these sites in…”
Section: Introductionmentioning
confidence: 99%